Pregnancy and Neonatal Outcomes After Exposure to Alprazolam in Pregnancy - Lee, Hyunji; Koh, Jae-Whoan; Kim, Young-Ah; Chun, Kyoung-Chul; Han, Jung Yeol; Hwang, Jong Hee; Choi, June-Seek; Joo, Sung Hong; Kwon, Hye-Young (Frontiers in Pharmacology, 2022)
Alprazolam is a commonly prescribed benzodiazepine for anxiety or panic disorder, even in pregnant women. Information on the safety of alprazolam during pregnancy is insufficient. We aimed to evaluate pregnancy and neonatal outcomes after exposure to alprazolam during pregnancy. A prospective study was conducted on 1,068 pregnancies from January 2000 to December 2019. Participants were recruited through the Korean Mother-Safe Program, a service providing information on drug-induced teratogenic risk during pregnancy and breastfeeding. Exposed (N=96) and non-exposed (N=629) women to alprazolam during pregnancy were selected and followed-up until delivery. Pregnancy outcomes, including spontaneous abortion, still birth, low birth weight (LBW), preterm birth, Apgar score (at 1 and 5 min), and malformations were measured and compared. Multivariable logistic regression was performed to examine the association between alprazolam exposure and outcomes. The mean age was 32.9 (SD 4.0) years in the alprazolam-exposed group and 31.8 (SD 3.8) years in the unexposed group (P=0.008). The alprazolam exposure group demonstrated a significantly higher likelihood of pregnancy and neonatal outcomes: spontaneous abortion (OR=2.38; 95%CI 1.20-4.69), LBW (OR=3.65; 95%CI 1.22-11.00), and Apgar score at 1 min ≤7 (OR=2.19; 95%CI 1.02-4.67). There was no significant difference in congenital abnormalities between the exposure and non-exposure groups. Our findings confirmed that alprazolam exposure during pregnancy was significantly associated with adverse pregnancy and neonatal outcomes, including spontaneous abortion, low birth weight, and Apgar score at 1 min ≤7. Alprazolam during pregnancy should be appropriately regulated and monitored.